TELAAH AWAL TEMUAN MERIAM KUNA DI SURABAYA - Danang Wahju Utomo (Balai Arkeologi Provinsi Sulawesi Selatan, 2010)
A cannon is any tubular piece of artillery that uses gunpowder or other usually explosive based propellants to launch a projectile. Cannon vary in caliber, range, mobility, rate of fire, angle of fire, and firepower; different forms of cannon combine and balance these attributes: varying degrees, depending on their intended use on the battlefield. The word cannon is derived from several languages, in which the original definition can usually be translated as tube, cane, or reed. In modern times, cannon has fallen out of common usage, usually replaced by